Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17134869
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Compassion, Subjective Happiness and Proactive Strategies on Kindergarten Teachers’ Work Engagement and Perceived Working Environment Fit

Abstract: Background: The current cross-sectional study examines a model that was designed to advance understanding of the interplay between compassion towards teachers expressed by teaching colleagues, subjective happiness, proactive strategies and kindergarten teachers’ levels of work engagement, and perceived working environment fit. Methods: The research was conducted with a sample of 319 full-time in-service kindergarten teachers at Italian public preschools—a context in which a few previous studies have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 103 publications
(129 reference statements)
1
11
0
1
Order By: Relevance
“…Subjective wellbeing was found to be moderately related to work engagement among Polish individuals [50]. A study conducted with a sample of 319 full-time in-service kindergarten teachers concluded that subjective wellbeing had a positive association with work engagement [51]. The hierarchical regression analysis in this study showed a signi cant positive correlation (b=0.182, p<0.01) between work engagement and subjective well-being, similar to other studies [52].…”
Section: Discussionsupporting
confidence: 85%
“…Subjective wellbeing was found to be moderately related to work engagement among Polish individuals [50]. A study conducted with a sample of 319 full-time in-service kindergarten teachers concluded that subjective wellbeing had a positive association with work engagement [51]. The hierarchical regression analysis in this study showed a signi cant positive correlation (b=0.182, p<0.01) between work engagement and subjective well-being, similar to other studies [52].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, it coincides with the ethnomusicological perspective that conceives of music as a socio-cultural phenomenon that requires cooperation and coordination [ 54 ]. This perspective would also contribute to broadening the theoretical basis that justifies the use of active methodologies in the classroom as opposed to more traditional models focused on theory, technique, and individual learning [ 89 , 90 , 91 , 92 ]. In further research, it would be useful to study not only the greater or lesser use of music, but also the methodology implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on teachers’ work engagement considered several work-related resources when addressing its antecedents ( Skaalvik and Skaalvik, 2014 ; Eldor and Shoshani, 2016 ; Minghui et al, 2018 ; Fiorilli et al, 2019b , 2020 ; Granziera and Perera, 2019 ; De Stasio et al, 2020 ). Such resources, for example, included social support at work ( Minghui et al, 2018 ; Fiorilli et al, 2019b ), person-job fit ( Rothmann and Hamukang’andu, 2013 ; Li et al, 2015 ), or career perspectives ( Timms and Brough, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This work aims at contributing to the studies focusing on the motivational process described by the JDR, thus individuating factors enhancing teachers’ engagement ( Li et al, 2015 ; Minghui et al, 2018 ; Zahed-Babelan et al, 2019 ; De Stasio et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%